DAYA SAING UMKM PERTANIAN-PENGOLAHAN-PERDAGANGAN BERDASARKAN LOGISTICAL-CROSSFUNCTIONAL DRIVERS - Sumarsono; Andhika Mayasari; Fatma Ayu N.F.A, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
A specific study of the competitiveness of MSMEs is needed based on the main sectors of Agriculture, Manufacturing, and Trade (AMT). They have different operational activities but dissimilar constraints to logistical-crossfunctional drivers (LCD) on supply chain competitiveness (SCC). The research objectives are: (1). To analyze relationship LCD, on the competitiveness of MSMEs AMT. (2). To examine the difference in the effect of LCD on the competitiveness of MSMEs AMT. The first results that the LCD aspect was significantly related to the SCC of MSMEs in sector manufacturing and trading, but not to agricultural. Three factors of LCD of agricultural MSMEs are not significant, namely inventory, information, and pricing. They indicate, weak role in shaping the SCC of agricultural MSMEs. The second result, no significant difference in the competitiveness of MSMEs AMT related to the effect of LCD. They mean the LCD both have an impact on driving the SCC of MSMEs AMT. So be competitive does not require different treatment in applying LCD to MSMEs AMT.